Product quality and worker quality - Abowd, John M. 1951-; Kramarz, Francis; Moreau, Antoine (1995)
We study the relation between product quality and worker quality using an economic model that, under certain conditions, provides a direct link between product price, product quality and work force quality. Our measures of product quality are the evolution in the detailed product price relative to its product group and the level of the product price relative to this group. Our worker quality measures are the firm's average person effect and personal characteristics effect from individual wage rates. We find a very weak, generally positive, relation between worker quality and product quality using detailed firm-level data from the French Producer Price Index surveys.
Keywords: Quality of products -- France; Wages and labor productivity -- France; Wirtschaftsmodell; Arbeit; Qualität; Produkt; Frankreich